ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI BERKARAKTER KELAS XI SMA NEGERI UNTUK STANDARISASI RPP DI KABUPATEN SOLOK - Gusdenti, Leni; Mulyati, Mulyati; Nerita, Siska (Pendidikan Biologi, 2013)
ABSTRACT Lesson plan (RPP) is a plan that describes about learning procedure to achieve the learning goals that determined in contents and standards outlined in the syllabus. However, there are many teachers who does not make a lesson plan (RPP) before learning process and there are still teachers who make a lesson plan from the last semester without adapted with characteristics of students and schools. Relationship with it, has been done analyzes lesson plan (RPP) character at eleventh (XI) grade biology of Senior High SchoolÂ  in distric Solok. The purpose of this research is to see standardization of lesson plan (RPP) made by the teacher of biology at eleventh (XI) grade Senior High Schoolin distric Solok suitable with the standard instrument developed by Mulyati, et.al. The kind of this research is descriptive research with sampling was stratified random sampling. This research showed the completeness of existing components (59%), which does not exist (41%). It can be concluded that lesson plan (RPP) of the teacher biology at Senior High Schoolin distric Solok was fairly standard (64,55%).Â